Characterization of the inflammatory response to four commercial bone graft substitutes using a murine biocompatibility model - Markel DC; Guthrie ST; Wu B; Song Z; Wooley PH (Dove Medical Press, 2012)
David C Markel1, S Trent Guthrie2, Bin Wu3, Zheng Song4, Paul H Wooley41Department of Orthopaedics, Providence Hospital and Medical Centers, Southfield, MI, 2Henry Ford Hospital, Detroit, MI, 3Department of Biomedical Engineering, Wayne State University, Detroit, MI, 4Orthopaedic Research Institute, Wichita, KS, USAAbstract: Bone grafting is utilized in nearly all orthopedic subspecialties and in most anatomic regions. Bone graft substitutes have the potential to offer similar efficacy as autogenous grafts without the morbidity of harvest. Several studies have noted the efficacy of new-generation bone substitute products, but few studies have evaluated their safety. This study characterizes and quantifies the inflammatory reaction to four different commercially available bone graft substitutes, which were examined using the in vivo murine air pouch biocompatibility model. One coralline hydroxyapatite product was chosen as an example of a purely osteoconductive material. Three demineralized bone matrix products were chosen to represent products that are both osteoconductive and osteoinductive. Samples were implanted in a murine air pouch and harvested after 14 days in situ. Pouch fluid was extracted, mRNA isolated, and reverse transcription polymerase chain reactions carried out to detect interleukin-1 gene expression as a marker for inflammation. In addition, multiple histological characteristics were examined to quantify cellular responses to the implanted materials. All bone graft substitutes induced a significant inflammatory response compared with negative controls. Histology and polymerase chain reaction data indicated that the level of inflammatory reaction was elevated in materials with a higher demineralized bone matrix to carrier proportion. The hydroxyapatite product generated a low inflammatory reaction. In conclusion, this study used an in vivo model of biocompatibility to demonstrate that a significant inflammatory reaction occurs when using implanted bone graft substitutes. When choosing a bone grafting method, surgeons should consider both the efficacy and safety of methods and materials used. Further studies are necessary to determine the ideal bone graft material to maximize efficacy while minimizing morbidity.Keywords: bone graft, biocompatibility, inflammation, animal model